2019
DOI: 10.3390/ijerph16162896
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Sustainable Development of Water Resources: A Social Welfare Maximization Game Model

Abstract: Water can carry a boat but can also overturn it (human societal sustainable development). Governments faced aquatic ecosystem restoration and preservation challenges following the establishment of the United Nations Sustainable Development Goals. This paper proposes a social welfare maximization game model to analyze the dominant strategy equilibrium of enterprise-1 and enterprise-2 based on welfare maximization under the total sewage emission control policy. Under the aforementioned control policy, a stricter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…(2) Promote the construction of a water-saving society e promotion of the development of a water-saving society [14] is the most effective way to address the core issue of my country's water resources. Most notably, this is manifested in the following ways: adjustment of the price system for residents' domestic water and agricultural water; technical transformation of industries with high water consumption, including the recommendation of watersaving equipment; centralized treatment of sewage; and utilization of seawater after desalination, among other things [15].…”
Section: Water Resources Audit and Sustainablementioning
confidence: 99%
“…(2) Promote the construction of a water-saving society e promotion of the development of a water-saving society [14] is the most effective way to address the core issue of my country's water resources. Most notably, this is manifested in the following ways: adjustment of the price system for residents' domestic water and agricultural water; technical transformation of industries with high water consumption, including the recommendation of watersaving equipment; centralized treatment of sewage; and utilization of seawater after desalination, among other things [15].…”
Section: Water Resources Audit and Sustainablementioning
confidence: 99%
“…Irrigation accounts for about 70% of GW abstraction annually and 40% of global total irrigation [6]. GW is facing a crisis of overexploitation and pollution due to population growth, expansion of industry and agriculture, and poor management [7][8][9][10][11]. Studies have shown that GW levels have generally declined globally, particularly in the Mid-Atlantic region of the United States, California's Central Valley, northern India, the Middle East, and the North China Plain (NCP) [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of applied mathematical models that can translate the behavior of variables in surface waters, especially urban ones, is important in the face of the loads of pollutants in the aquatic environment (CUNHA et al, 2006;GUO et al, 2019;TEODORO et al, 2013), and they can be used to predict future scenarios. Therefore, mathematical models can be used for instructing management actions that support decisions related to the functional perenniality of environmental services, offered by urban waters.…”
Section: Introductionmentioning
confidence: 99%